RESPONSIBLE DIGITAL TRANSFORMATION IN MSMEs: BALANCING TECHNOLOGY ADOPTION, GOVERNANCE, AND CUSTOMER VALUE - Diah Fatma Sjoraida; Finny Redjeki (Journal of Jabar Economic Society Networking Forum, 2025)
This conceptual paper develops an integrative framework for responsible digital transformation in MSMEs in micro, small, and medium enterprises (MSMEs). It synthesizes established literature on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial ecosystems. The analysis explains how technology fit, digital governance, employee learning, customer value, and proportionate risk control can be organized into proportionate managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The framework proposes diagnosis, capability mapping, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention as a cumulative cycle. Implications are developed for owner-managers, support institutions, and future empirical research.